Education on how to brush teeth with animated videos for student of TPA Al-Barokah - Nyka Dwi Febria; Multia Ranum Sari; Dian Yosi Arinawati; Pipiet Okti (Universitas Muhammadiyah Magelang, 2022)
Dental caries disease still shows a high prevalence in developing countries, including Indonesia and generally occurs in children. This is due to the lack of dental and oral hygiene. This problem can be solved by brushing teeth properly. Frequency and the correct way of brushing teeth can prevent dental caries in children. Therefore, education is needed on how to brush teeth properly. The media used in counseling how to brush teeth properly is animated video. The purpose of this program is to increase children's knowledge regarding dental and oral hygiene, so that it is expected to become a habit in everyday life. The counseling was conducted at the Al-Barokah Piring TPA, Pundong, Bantul. Counseling begins with a pretest and ends with a posttest to determine the increase in children's knowledge regarding dental and oral hygiene. The results from this program are animated videos can increase children's interest in learning and there is an increase in children's knowledge after counseling related to dental and oral hygiene.